On the possibility of reducing the pile-up effect on the Berkovich instrumented indentation tests. (February 2017) - Chang, Chao; Garrido, M.A.; Ruiz-Hervias, J.; Rodríguez, J.
Abstract: In this study, an alternative instrumented indentation methodology was presented. Based on the evolution of the contact stiffness and indentation load with the penetration depth, the determination of the actual Young´s modulus of elastic-plastic materials through Berkovich instrumented indentation tests has been explored. In addition, the proposed methodology seems to be less sensitive to the pile-up phenomenon, and also allows us to assess the effect of the indenter tip (Berkovich) rounding on the experimental data. The methodology was validated through a series of Berkovich indentation tests on five commercial elastic-plastic materials: carbon steel (F-114), aluminium (Al-1050), brass, polycrystalline tungsten and fused silica. The Young´s modulus of these materials, obtained through the proposed methodology, was compared with those determined by other indentation methodology and with those obtained by traditional methods (i.e. tensile tests and impulse excitation tests) and it was found that they are very similar to the ones corresponding to traditional methods. Highlights: Sharp instrumented indentations were carried out on five elastic-plastic materials. An analytical equation is proposed to evaluate Young´s modulus and hardness. The proposed methodology gives accurate values of Young´s modulus in elastic-plastic materials. The effects of the plasticity phenomena such as pile-up were reduced.